THE CORRELATION BETWEEN ACID FAST BACILLI SPUTUM EXAMINATION AND CHEST RADIOLOGY IN PULMONARY TUBERCULOSIS PATIENTS AT RUMAH SAKIT UMUM DAERAH DR. H. ABDUL MOELOEK 2021 - Pangestu, Farhan Ridho (Universitas Aisyah Pringsewu, 2023)
The Correlation Between Acid Fast Bacilli Sputum Examination And Chest Radiology In Pulmonary Tuberculosis Patients At Rumah Sakit Umum Daerah Dr. H. Abdul Moeloek 2021. Mycobacterium tuberculosis is a bacterium that causes an infectious disease called Tuberculosis (TB). In 2021, Indonesia currently has the third highest number of TB cases in the world. Sputum examination and chest radiology are the main diagnostic tools for diagnosing pulmonary TB. This study aims to determine the relationship between sputum examination and chest radiology in TB patients. The type of this research was analytic observational which was carried out using the cross sectional method using secondary data from the medical records of patients who were confirmed to be infected with pulmonary tuberculosis at RSUD Dr. H. Abdoel Moeloek City of Bandar Lampung in 2020-2022 with a total sample of 136. Data were analyzed using statistical software to see the frequency of data and continued with bivariate analysis using the chi-square method ? = 0.05. The results showed AFB+1 with minimal lesions 18 out of 61, AFB +2 with moderate lesions 21 out of 51, and AFB +3 far advanced lesions 17 out of 24. The results of Chi-Square analysis obtained p value = 0.023. There is a relationship between examination of AFB sputum and chest X-ray images in pulmonary TB patients at RSUD Dr. H. Abdul Moeloek Lampung Province in 2020-2022.